Plasticity and Beyond Microstructures, Crystal-Plasticity and Phase Transitions - Schröder, Jörg; Hackl, Klaus (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2014)
The book presents the latest findings in experimental plasticity, crystal plasticity, phase transitions, advanced mathematical modeling of finite plasticity and multi-scale modeling. The associated algorithmic treatment is mainly based on finite element formulations for standard (local approach) as well as for non-standard (non-local approach) continua and for pure macroscopic as well as for directly coupled two-scale boundary value problems. Applications in the area of material design/processing are covered, ranging from grain boundary effects in polycrystals and phase transitions to deep-drawing of multiphase steels by directly taking into account random microstructures.